2016
DOI: 10.1016/j.jhydrol.2016.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Energy and water balance response of a vegetated wetland to herbicide treatment of invasive Phragmites australis

Abstract: The energy and water balance of a Phragmites australis dominated wetland in south central Nebraska was analyzed to assess consumptive water use and the potential for "water savings" as a result of vegetation eradication via herbicide treatment. Energy balance measurements were made at the field site for two growing seasons (treated and untreated), including observations of net radiation, heat storage, and sensible heat flux, which was measured using a large-aperture scintillometer. Latent heat flux was calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 59 publications
0
11
0
1
Order By: Relevance
“…This fluctuation affects riparian vegetation, often at the expense of historically native species (Mortenson & Weisberg, 2010;Mykleby et al, 2016;Richardson et al, 2007;Rood et al, 2007), as we have demonstrated. This fluctuation affects riparian vegetation, often at the expense of historically native species (Mortenson & Weisberg, 2010;Mykleby et al, 2016;Richardson et al, 2007;Rood et al, 2007), as we have demonstrated.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…This fluctuation affects riparian vegetation, often at the expense of historically native species (Mortenson & Weisberg, 2010;Mykleby et al, 2016;Richardson et al, 2007;Rood et al, 2007), as we have demonstrated. This fluctuation affects riparian vegetation, often at the expense of historically native species (Mortenson & Weisberg, 2010;Mykleby et al, 2016;Richardson et al, 2007;Rood et al, 2007), as we have demonstrated.…”
Section: Discussionmentioning
confidence: 62%
“…Over the past century, riparian ecosystems across the United States have experienced drier conditions due to climatic fluctuation, streamflow regulation, vegetation cover change, agricultural practices, or a combination thereof (Huddle et al, 2011;Mykleby et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations